Comparison of Anterior Segment Optical Coherence Tomography Bleb Grading, Moorfields Bleb Grading System, and Intraocular Pressure After Trabeculectomy. Issue 5 (May 2017) - Wen, Joanne C.; Stinnett, Sandra S.; Asrani, Sanjay
Abstract : Purpose: To compare a novel anterior segment optical coherence tomography (AS-OCT) bleb grading system with a clinical bleb grading system and both with intraocular pressure (IOP) following trabeculectomy surgery. Materials and Methods: A novel AS-OCT grading system based on bleb size and internal reflectivity was developed. An imaging center was tasked with masked grading of AS-OCT images acquired by multiple surgical sites at postoperative week (POW) 2, postoperative month (POM) 4, 6, and 12, respectively. The Moorfields Bleb Grading System was used by another independent imaging center to grade clinical photos. The results of the 2 grading systems were compared and correlated with IOP. Results: Blebs of 124 eyes were assessed in this study. Higher (worse) AS-OCT bleb grades was significantly associated with: decreased bleb height at POM4, 6, and 12 ( P <0.001, 0.001, and 0.0001), increased central bleb vascularity at POM4 and 12 ( P =0.0026;0.036) and decreased maximal bleb area at POM6 and 12 ( P =0.026; 0.01). A higher AS-OCT bleb grade correlated with a higher IOP at POM4 and 6 ( P =0.004; 0.02), though no longer significant at POM12 ( P =0.1). Increased maximum bleb vascularity was associated with increased IOP at POM4 ( P =0.003) though none of the remaining MGBS parameters correlated significantly with IOP. Eyes with a final IOP of ⩽12 mm Hg had significantly lower AS-OCT bleb grades at POM6 ( P =0.045). Conclusion: A novel AS-OCT bleb grading system correlated well with a number of Moorfields Bleb Grading System variables throughout the 1-year postoperative period. Although the AS-OCT grades also correlated well with IOP throughout most of the postoperative period, it was limited in their abilities to predict final IOP.